2020
DOI: 10.1371/journal.ppat.1008529
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan depletes the membrane potential in Pseudomonas aeruginosa biofilms inhibiting aminoglycoside induced adaptive resistance

Abstract: Biofilm-based infections are difficult to treat due to their inherent resistance to antibiotic treatment. Discovering new approaches to enhance antibiotic efficacy in biofilms would be highly significant in treating many chronic infections. Exposure to aminoglycosides induces adaptive resistance in Pseudomonas aeruginosa biofilms. Adaptive resistance is primarily the result of active antibiotic export by RND-type efflux pumps, which use the proton motive force as an energy source. We show that the protonophore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 107 publications
(318 reference statements)
0
18
0
Order By: Relevance
“…Replacement of saturated with unsaturated fatty acids is linked with the reduced membrane permeability and CIP uptake in PA-R strains and clinically multidrug-resistant strains. Triclosan can deplete the membrane potential in P. aeruginosa biofilms inhibiting aminoglycoside-induced adaptive resistance (Maiden and Waters, 2020 ), but we found that triclosan promotes the alteration of the fatty acid metabolome of PA-R to return to that of PA-S and, thereby, elevates CIP-mediated killing by increasing membrane permeability and CIP uptake; this discrepancy may suggest that triclosan regulates antibiotic effect through different mechanisms. Our results suggest that the biosynthesis of fatty acids-related CIP resistance is mostly attributed to membrane permeability.…”
Section: Discussionmentioning
confidence: 57%
“…Replacement of saturated with unsaturated fatty acids is linked with the reduced membrane permeability and CIP uptake in PA-R strains and clinically multidrug-resistant strains. Triclosan can deplete the membrane potential in P. aeruginosa biofilms inhibiting aminoglycoside-induced adaptive resistance (Maiden and Waters, 2020 ), but we found that triclosan promotes the alteration of the fatty acid metabolome of PA-R to return to that of PA-S and, thereby, elevates CIP-mediated killing by increasing membrane permeability and CIP uptake; this discrepancy may suggest that triclosan regulates antibiotic effect through different mechanisms. Our results suggest that the biosynthesis of fatty acids-related CIP resistance is mostly attributed to membrane permeability.…”
Section: Discussionmentioning
confidence: 57%
“…Surprisingly, although this effect was specific to P. aeruginosa in biofilms (no synergy was observed in planktonic bacteria), the combination did not seem to increase biofilm dispersion (81). Instead, the compound appears to disrupt the proton-motive force that is used to power RND pump-mediated drug efflux, increasing intracellular tobramycin concentrations (85). This result remains somewhat intriguing, since efflux is generally accepted as the mechanism of P. aeruginosa resistance to triclosan (86,87).…”
Section: Methodsmentioning
confidence: 97%
“…During experimental evolution, the lid with pegs can easily be transferred to a new 96-well plate and biofilms can be dispersed from the pegs via sonication. The resulting cell suspensions can then be used to start biofilm formation on pegs on a new lid 77 . A conceptually-similar system (FlexiPeg) was recently developed and used to study competition and fitness in biofilms 78 , 79 .…”
Section: Tools To Study Experimental Evolution In Biofilmsmentioning
confidence: 99%